Design of Physics Teaching Aids on Arduino Uno-based parallel Series Circuits - Sabila, Siska Rima; Kaneishia, Sabrina; Amanda, Silvia Aprilia; Rizki, Putri Annisa; Zulfa, Indana; Harijanto, Alex; maryani, Maryani (Universitas Islam Negeri (UIN) Mataram, 2024)
This study aims to develop Arduino-based parallel series circuit teaching aids to facilitate students in understanding the concepts of Ohm's Law. The method used in this research is to use research and development procedures (Research and Development) with Nieveen's description. The design of teaching aids in this study uses the help of Arduino Uno R3 so that measurements can be made automatically. The props designed by researchers use a 30 ampere acs712 current sensor. Based on the results of the data obtained, the relationship between the voltage and the current produced is directly proportional. This is evidenced when the series circuit given a voltage of 6 volts produces a current of 1.82 A when given a voltage of 7.6 volts produces a current of 2.08 A, and when given a voltage of 9.25 volts produces a current of 2.34 A. Likewise, in parallel circuits, the relationship between voltage and current is also directly proportional. When the voltage given is 6 volts, it produces a current of 1.04 A, when the voltage is 7.6 volts, it produces a current of 1.30 A, when the voltage is 9.25 volts, it produces a current of 1.56 A. Based on these data, it can be interpreted that the greater the voltage given, the greater the current that will be generated. Thus, the research and development of Arduino-based parallel series circuit teaching aids is by the existing literature. This Arduino-based parallel series circuit trainer can be said to have a relatively good level of measurement accuracy. that the props that have been made can work well in series circuits and parallel circuits. The parallel series circuit is arranged using an Arduino uno R3 microcontroller and uses a 30-ampere acs 712 current sensor. The level of measurement accuracy produced is relatively good at around 88%. according to experts, the percentage of similarity of 80%-90% can be said to be good. Thus, this Arduino-based series parallel circuit trainer can be said to have a relatively good level of measurement accuracy.